The Influence Of Product Quality and Price On Interest To Buy Dompu Special Honey At Ikm Mart - Sudarmiatin Sudarmiatin; Ega Saiful (CV. Syntax Corporation Indonesia, 2022)
ABSTRACT This research is a quantitative research with a case study on the Dompu community. With the aim of knowing the effect of product quality and price on interest in buying honey. The variables studied were Product Quality (X1 ), Price (X2 ) and Purchase Interest (Y). This study uses a sample of 60 respondents with sampling using accidental sampling method. The method used in this research is Multiple Linear Regression Analysis. This study aims to: (1) find out how much product quality affects buying interest; (2) find out how much the price has an effect on buying interest; (3) how much product quality and price together influence buying interest. This research method is a quantitative research. The sampling technique used was accidental sampling, and the number of samples used was 60 respondents. The data collection technique is primary data or data taken directly from respondents through questionnaires. The analysis technique uses multiple linear regression. The independent variables in this study are product quality and price, while the dependent variable is buying interest. The results show that: (1) Product quality affects buying interest with a contribution of 1.152 or 11.52%, (2) Price affects buying interest with a contribution of 1.112 or 11.12%, and (3) quality of information and trust consumers are jointly influential with a contribution of 10.53%.